Respuesta :
Answer:
y + 1 = 3(x - 1)
Step-by-step explanation:
The given point is (1,-1) meaning that x1 = 1 and y1 = -1
The slope of this line is m = 3 because we go up 3 and over to the right 1 (eg: go from the point (1,-1) to (2,2) to see this in action)
Plug these three pieces of info into the point slope formula below
y - y1 = m(x - x1)
y - (-1) = 3(x - 1)
y + 1 = 3(x - 1)
Answer:
y+1 = 3(x-1)
Step-by-step explanation:
We need to find the slope
We have one point (1,-1) Another point is (2,2)
Slope = (y2-y2)/(x2-x1)
= (2--1)/(2-1)
= (2+1)/(2-1)
= 3/1
The slope is 3
Point slope for of a line is given by
y-y1 = m(x-x1)
We are to use the point (1,-1)
y--1 = 3(x-1)
y+1 = 3(x-1)